Embossed transparent electrodes assembled by bubble templates for efficient flexible perovskite solar cells. (November 2021) - Yang, Yongrui; Min, Fanyi; Qiao, Yali; Li, Zheng; Vogelbacher, Florian; Liu, Zhaoxin; Lv, Wenkun; Wang, Yang; Song, Yanlin
Abstract: Flexible perovskite solar cells are promising power source candidates in wearable and portable electronics. However, the performance of flexible perovskite solar cells still lags the values reported in rigid devices. This issue is mainly due to the lack of suitable electrodes which possess low sheet resistance, high optical transmittance, and smooth surface. Here, we proposed a flexible electrode based on solution-processed silver grids. With the patterned micro-bubbles as templates, high-resolution sliver grids electrodes were fabricated, which showed a sheet resistance of 7.9 Ω/sq and optical transmittance over 85% (including the substrate, from 375 nm to 900 nm). Besides, the embossed sliver grids can assist the growth of perovskite crystals and provide localized channels for charge carrier transport. The corresponding flexible perovskite solar cells based on these flexible sliver grids electrodes achieved a power conversion efficiency of 18.49% with remarkable flexibility, which enhanced about 20% compared to the control devices. Graphical Abstract: An embossed transparent electrode based on high-definition flexible Ag grids (FAGs) was fabricated by a self-assembled method with patterned bubbles as templates. The flexible transparent electrode based on highly ordered Ag grids presented high optical transmittance (>85% including substrate, from 375 to 900 nm) and low sheet resistance ( 7.9 Ω/sq). The microstructures on the surface of the FAGs can optimize the film morphology of perovskite thin films by slowing down the nucleation process of perovskite precursor. In addition, the highly ordered embossed Ag grids served as localized channels for charge carrier transport, leading an efficient charge extraction on the interface between charge transfer layer and perovskite layer. The corresponding flexible perovskite solar cells based on the FAGs electrodes achieved a power conversion efficiency of 18.49% with remarkable flexibility, which was about 20% higher than the control devices. ga1 Highlights: An embossed transparent electrode based on high-definition flexible Ag grids (FAGs) was fabricated by a printable self-assembled approach with patterned bubbles as templates. The embossed Ag grids also served as localized channels for charge carrier transport and resulted in an efficient charge extraction. The corresponding flexible perovskite solar cells achieved a power conversion efficiency of 18.49%.